2021
DOI: 10.3390/polym13060850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molecular Weight of Functionalized Liquid Butadiene Rubber as a Processing Aid on the Properties of SSBR/Silica Compounds

Abstract: Liquid butadiene rubber (LqBR) which used as a processing aid play a vital role in the manufacturing of high-performance tire tread compounds. However, the studies on the effect of molecular weight, microstructure, and functionalization of LqBR on the properties of compounds are still insufficient. In this study, non-functionalized and center-functionalized liquid butadiene rubbers (N-LqBR and C-LqBR modified with ethoxysilyl group, respectively) were synthesized with low vinyl content and different molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Figure 2 and Figure 3 , and Table 4 show the results of GPC and 1 H NMR of the polymerized LqBRs. Kim et al, reported that most LqBRs can be crosslinked to the base polymer by sulfur when the molecular weight of the LqBR is 25,000 g/mol or higher [ 19 ]. In addition, Salort et al, reported that low-molecular-weight di-functionalized LqBRs can be crosslinked to the base polymer by sulfur through higher molecular-weight structure formation by self-condensation [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2 and Figure 3 , and Table 4 show the results of GPC and 1 H NMR of the polymerized LqBRs. Kim et al, reported that most LqBRs can be crosslinked to the base polymer by sulfur when the molecular weight of the LqBR is 25,000 g/mol or higher [ 19 ]. In addition, Salort et al, reported that low-molecular-weight di-functionalized LqBRs can be crosslinked to the base polymer by sulfur through higher molecular-weight structure formation by self-condensation [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient viscosity and shearing force are required during the mixing process to achieve excellent silica dispersion within the compound [ 1 , 19 ]. Due to the fact that LqBRs, which have higher molecular weights than TDAE oils (molecular weight < 500 g/mol), possess higher viscosity, high peak torque values were obtained in the first stage of the mixing process, as shown in Figure 4 and Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations